2011
DOI: 10.1088/2041-8205/743/1/l2
|View full text |Cite
|
Sign up to set email alerts
|

Transition Disk Chemistry and Future Prospects With Alma

Abstract: We explore the chemical structure of a disk that contains a large central gap of R ∼ 45 AU, as is commonly seen in transitional disk systems. In our chemical model of a disk with a cleared inner void, the midplane becomes revealed to the central star so that it is directly irradiated. The midplane material at the truncation radius is permissive to reprocessed optical heating radiation, but opaque to the photo-dissociating ultraviolet, creating an environment abundant in gas-phase molecules. Thus the disk midpl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 37 publications
3
44
0
Order By: Relevance
“…The survival of molecules like CO and the chemistry of other species in dust-free cavities in transitional disks has been modeled by Bruderer 240 241 and is being tested against ALMA observations for the case of H 2 CO 242 . Molecules produced in ices may be observable as well when the disk midplane is exposed to the stellar photons at the outer edge of the cavity and molecules can be desorbed 243 . Altogether, these data form a vivid illustration and warning that gas and dust grains do not necessarily follow each other but that they need to be treated separately in the models.…”
Section: Protoplanetary Disksmentioning
confidence: 99%
“…The survival of molecules like CO and the chemistry of other species in dust-free cavities in transitional disks has been modeled by Bruderer 240 241 and is being tested against ALMA observations for the case of H 2 CO 242 . Molecules produced in ices may be observable as well when the disk midplane is exposed to the stellar photons at the outer edge of the cavity and molecules can be desorbed 243 . Altogether, these data form a vivid illustration and warning that gas and dust grains do not necessarily follow each other but that they need to be treated separately in the models.…”
Section: Protoplanetary Disksmentioning
confidence: 99%
“…The case of the observability of simulated line emission has been investigated A&A 549, A97 (2013) by Semenov et al (2008), Regály et al (2010), and Cleeves et al (2011). For the infrared wavelength range, the observability of planet-induced, large-scale disk structures was explored by Varnière et al (2006), Wolf & D'Angelo (2005), and Jang-Condell (2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the resulting CO column densities are still not consistent with observations. As indicated by Cleeves et al (2011), the disk midplane in the gap region can be irradiated by the stellar radiation and X-rays. Thus, CO would not be frozen out onto grains, which would result in better gap detection rate thanks to higher contrast.…”
Section: Distribution Of the Different Molecular Speciesmentioning
confidence: 99%
“…Dutrey et al (2008) used spatially unresolved but spectroscopically resolved line observations to trace inner cavities due to the radial dependence of the (Keplerian) velocity field. Cleeves et al (2011) demonstrated the feasibility of detecting a huge inner cavity (R ∼ 45 AU) using molecular lines (CO, H 2 CO 2 ). Using ALMA, Casassus et al (2013) were able to image multiple molecular gas species within the dust free inner hole of HD 142527 and to utilize the varying optical depths of the different species to detect a flow of gas crossing the gap opened by a planet.…”
Section: Introductionmentioning
confidence: 99%